Microbial profile their antibiog:. am pattern in cervico-uterine contents and conception rate following treatment in repeat breeder crossbred cows - CHANDRAKAR, DEEPAK; TIWARl, R P; AWASTHl, M K; HIRPURKAR, S D (The Indian Journal of Animal Reproduction, 2023)
. The overall frequencies of different bacterial isolates identified from uterine fluid of repeat breeding crossbred cows were Staph. aureus(29.16%), E. coli (20.83%), C. pyogenes ( 16.66%), Ps. aeruginosa( 16.66%), Streptococcus ( 12.5% ), and Proteus ( 4.16% ). The antibiotic sensitivity pattern of these bacterial isolates revealed that chloramphenicol (91.6%) was most effective drug followed by gentamicin (70.8% ). However, lower sensitivity was evident against oxytetracyclin ( 37.5%), cephalexin (33.3%) and streptomycin(33.3%) where as ampicillin and penicillin did not show any sensitivity (0.0%). The animals treated based on sensitivity test, with chloramphenicol and gentamicin revealed 80% and 70% conception rate. respectively.